Konsep Model Pembelajaran Luar (Learning, Understanding, Assessment, Reward) Untuk Meningkatkan Kemandirian Belajar - Audriansyah, Lulu Ulfah (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
Increasing students' learning independence is a crucial goal in sustainable educational development. This article discusses the development of the LUAR learning model (Learning, Understanding, Assessment, and Reward) which aims to increase students' learning independence. This research adopts a qualitative approach to explore the design concept of the learning model to be developed. The stages start from reviewing various literature regarding existing learning theories and learning models. Next, an analysis is carried out regarding the advantages and disadvantages of existing learning models so that they can form a conceptual basis for developing new learning model designs. Through the development of the LUAR learning model, it is hoped that it can create a learning environment that encourages students' learning independence to achieve success in education.